(untitled) (Experimental biology, 2016)
The article provides an analysis of the species composition of the family Caryophyllaceae Trans-Ili Alatau. Revealed that the study area from the family Caryophyllaceae common 89 species belonging to 29 genera. Leading position in the taxonomic composition occupy large genus Silene (21 species), Cerastium (10 species), Stellaria (8 species). In assessing the diversity of the family Caryophyllaceae Trans-Ili Alatau shown that in the region of investigation in this family of environmental types found 3 groups with respect to moisture: mesophytes, mezokserofity, xeromesophyte. As a result, environmental analysis flora Trans-Ili Alatau, which is based on the classification adopted by the Group in relation to soil moisture, revealed that most of the up mezokserofity (50 species, 58.8%). Analysis of the types of life forms Trans-Ili Alatau showed predominant are perennials (59 species or 66,29%). It was revealed that in the flora of the Trans-Ili Alatau of the family Caryophyllaceae found 21 economically important species. Of these, the largest number of species - it is medicinal plants. In the flora of the Trans-Ili Alatau of the family Caryophyllaceae were found 1 endemic species (Silene tianschanica), which relates to rare species.